Bernard-Burow flap unilateral with cheek mucosa “cutback” for treatment of lower lip tumor: a case report - Sergio Antonio Saldanha Rodrigues; Marcelo Martins Casagrande; Thalita Ezequiel de Souza; Gustavo Moreira Costa de Souza; Armando Chiari (Revista Brasileira de Cirurgia Plástica)
Lip cancer corresponds to 25-30% of all oral cancers, with the lower lip being more frequent. Squamous cell carcinoma (SCC) is the most common subtype, with smoking as one of the main risk factors. The report demonstrates a simple and effective technique for SCC's surgical treatment on a smoking patient's lower lip. Even in a defect larger than 50% of the initial lip diameter, the unilateral Bernard-Burow flap proved feasible. The addition of "cutback" in the mucosa and parsimonious dissection by planes may have provided a good aesthetic and functional evolution since it determined tension relief on the sutures. The less complex execution of this reconstruction, compared to other techniques, can guarantee a good alternative to decrease postoperative morbidity in this type of surgery.